Forming and deformation behavior of the ultrafine-grained Zr-1Nb alloy; Steel in Translation; Vol. 45, iss. 2 - Grabovetskaya G. P. Galina Petrovna; Mishin I. P. Ivan Petrovich; Stepanova E. N. Ekaterina Nikolaevna; Chernov I. P. Ivan Petrovich (2015, 2015)
Title screen